(untitled) (Mustansiria Dental Journal, 2018)
Salivary sex hormones (estradiol/ progesterone) levels may rise dramatically & may affect the periodontal health during pregnancy. The aim of this study was to measure the level of estradiol &progesterone in stimulated saliva of pregnant women & its correlation to periodontal status in comparison to non pregnant women. A total of 26 women of the age group 20-24yr. attending the maternal & child health care in the medical city hospital were selected at the 3rd trimester of pregnancy & another 26 unmarried women were selected rand only. Saliva had been collected for analysis of estradiol & progesterone & periodontal status had been evaluated using plaque index (PlI), gingival index (GI), probing depth (PD) & clinical attachment level (CAL), t-test, X2 & correlation coefficient were used where indicated. The results revealed a significant difference in the mean PlI & GI among pregnant & control groups. Pregnant women showed deeper pocket & more attachment loss & a high mean of salivary sex hormones than control group with significant differences. The results also revealed a positive correlations between probing depth, clinical attachment level & salivary sex hormones while there was no significant weak correlation between PlI, GI with salivary sex hormones. All the periodontal parameter & salivary sex hormones in this study were higher value in pregnant women than non pregnant with significant differences. More strong positive correlations were found between PD, CAL with salivary sex hormones & weak correlations with PlI & GI.